Blockchain-Based Confidential Multiparty Contract Signing Protocol Without TTP Using Elliptic Curve Cryptography. (2nd August 2021) - Payeras-Capellà, M Magdalena; Mut-Puigserver, Macià; Cabot-Nadal, Miquel À; Huguet-Rotger, Llorenç
Abstract: Signed information is difficult to manage and this difficulty is even bigger when pieces of signed digital information have to be exchanged in an atomic procedure. Multiparty contract signing is an application of fair exchange of values, where the information to be exchanged are signed versions of a contract. Traditionally, this trust service requires the involvement of a trusted third party (TTP). This is a point of weakness for the generalization of the use of electronic contract signing protocols. Another usual problem for multiparty contract signing is that the protocols for multiparty exchanges are far more complex that those for two-party exchanges. Additionally, it is common that the signers demand protocols that assure the confidentiality of the contract. In this proposal blockchain-based technologies and smart contracts are used to obtain a protocol for electronic contract signing that does not need a TTP in any stage of the procedure. The protocol satisfies the ideal requirements for the contract signing service, even allowing the signature of confidential contracts. Moreover, the proposed solution is far more efficient than previous solutions for fair exchange protocols using blockchain presented up to the date thanks to the use of elliptic curve cryptography.